Relationship between geo-cultural identity and leadership characteristic preferences of followers in a virtual environment - Howard, Tom, author; Geroy, Gary, advisor; Morgan, George, committee member; Yang, Ray, committee member; Harbour, Cliff, committee member (Colorado State University. Libraries, 2004)
Advances in technology, transportation, and changing attitudes of working in other cultures have enabled companies to compete in the global marketplace. To create, develop, and manage geographically and culturally dispersed teams, organizations are tasked with understanding the multi-faceted dimensions of a team working virtually. This study was undertaken to explore the relationship between geo-cultural identity and leadership characteristic preference of followers in a virtual environment. A review of earlier research identified five leadership characteristics that were tested in this study - communication, technical skills, trust / relationship building, vision, and collaboration. Information was gathered on how participants ranked these five leadership characteristics, and on the participants' perception of which characteristic was most important to a manager in each of four geo-cultural regions. The participant pool was virtual team members who worked for multi-national companies. Twenty companies participated. There were sixty-two usable responses - forty-nine from North America, ten from Latin America, three from Europe, and none from Asia Pacific. Descriptive and inferential statistics reported that overall, the participants ranked the Communicative and the Trust / Relationship Building leadership characteristics the most significant. The participants ranked the Visionary and Collaborative leadership characteristics third and fourth and the Technological leadership characteristic fifth. The answers to the qualitative question at the end of the survey lent support to the quantitative analysis. Although the North American participants ranked the five leadership characteristics similarly to the overall group, the Latin American participants ranked Communicative first and the remaining four not significantly different. The participants' perception varied of which leadership characteristic was most important to a manager in each region. Participants perceived that Communicative was most important to a North American manager and Trust / Relationship Builder most important to a Latin American manager. To a European manager, the participants perceived that Trust / Relationship Builder and Collaborative were equally important, and that Communicative and Trust / Relationship Builder were equally important to an Asian manager. The study could not definitively answer the research question; however, as the study was exploratory in nature, it did provide insight into those leadership characteristics which are important to members of virtual teams.
Keywords: correlation analysis; studies; cultural relations; cultural differences; collaboration; multiculturalism and pluralism